Deprescribing Potentially Inappropriate Preventive Cardiovascular Medication: Barriers and Enablers for Patients and General Practitioners. (June 2016) - Luymes, Clare H.; van der Kleij, Rianne M. J. J.; Poortvliet, Rosalinde K. E.; de Ruijter, Wouter; Reis, Ria; Numans, Mattijs E.
Background: The use of preventive cardiovascular medication by patients with low cardiovascular disease (CVD) risk is potentially inappropriate.Objective: The aim of this study was to identify barriers to and enablers of deprescribing potentially inappropriate preventive cardiovascular medication experienced by patients and general practitioners (GPs).Methods: A total of 10 GPs participating in the ECSTATIC trial (Evaluating Cessation of STatins and Antihypertensive Treatment In primary Care) audiotaped deprescribing consultations with low-CVD-risk patients. After initial conventional content analysis, 2 researchers separately coded all barriers to and enablers of deprescribing medication using framework analysis. We performed a within-case and cross-case analysis to explore barriers and enablers among both patients and GPs.Results: Patients (n = 49) and GPs (n = 10) expressed barriers and enablers with regard to the appropriateness of the medication and the deprescribing process. A family history for CVD was identified as a barrier to deprescribing medication for both patients and GPs. Patients feared possible consequences of deprescribing and were influenced by the opinion of their GP. Additionally, a presumed disapproving opinion from specialists influenced the GPs' willingness to deprescribe medication.Conclusions: Patients appreciated discussing their doubts regarding deprescribing potentially inappropriate preventive cardiovascular medication. Furthermore, they acknowledged their GP's expertise and took their opinion toward deprescribing into consideration. The GPs' decisions to deprescribe were influenced by the low CVD risk of the patients, additional risk factors, and the alleged specialist's opinion toward deprescribing. We recommend deprescribing consultations to be patient centered, with GPs addressing relevant themes and probable consequences of deprescribing preventive cardiovascular medication.